Optimizing the role of posyandu through nutrition huts in the context of prevention and accelerating the reduction of stunting at the rural level in Jombang District, East Java Indonesia - Hariyono, Hariyono; Ayu Megasari, Ni Luh; Setyowati, Dewi; Madusekar, Nila (Institute of Accounting Research and Novation (IARN), 2023)
Reducing the stunting rate has been declared a national priority program. The government continues to move to organize the tools for accelerating stunting prevention and formulating the 2018-2024 National Strategy for the Acceleration of Stunting Prevention. Community nutrition counseling is one of the strategic steps that can be taken to improve health status and optimize the role of Posyandu as a health service facility for the community at the grassroots level. Participants in this activity were community health cadres, community leaders and communities with children under five who have stunting risk factors in Bulurejo Village, Diwek District, Jombang Regency. The implementation method includes the preparation, implementation, and evaluation stages. The results of community service activities were that more than half of the respondents (53%) were aged 20-25 years, all respondents were female, the education level of most of the respondents (83%) was high school/equivalent and most (75%) of the respondents had jobs as Housewife. Referring to the requirements for cadres, the ability to read and write is one of the requirements to become a cadre so that the elementary education level meets the cadre requirements. In addition, the type of work most cadres are housewives (87.5%). Knowledge about stunting and nutrition huts before being given training more than half had poor knowledge (56%), knowledge about stunting and nutrition huts after being given training most had good knowledge (63%). This community service program has initiated the formation of a nutrition hut at the toddler posyandu in Bulurejo Village, Diwek District. In addition, there has been an increase in the knowledge and skills of cadres to carry out early detection of stunting using a Z score.